1997
DOI: 10.1523/jneurosci.17-05-01776.1997
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Transcription Factor CREB in Rat Spinal Cord after Formalin-Induced Hyperalgesia: Relationship toc-fosInduction

Abstract: The involvement of cAMP-responsive element-binding protein (CREB) signaling in tissue injury-induced inflammation and hyperalgesia has been characterized by measuring phosphorylation of CREB at serine-133 (CREB Ser133) using a specific antibody. In the unstimulated state, unphosphorylated CREB was observed in most nuclei of spinal neurons except for motor neurons, where only a small portion of neurons were stained. A few dorsal root ganglion (DRG) neurons were also CREBpositive. After a unilateral injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
153
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(164 citation statements)
references
References 57 publications
9
153
2
Order By: Relevance
“…In the early stages of inflammation (Ji and Rupp 1997) and sciatic nerve injury (Ma and Quirion 2001), the phosphorylation of CREB is increased. Furthermore, this transcription factor regulates long-lasting effects of NO in neurons (Contestabile 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of inflammation (Ji and Rupp 1997) and sciatic nerve injury (Ma and Quirion 2001), the phosphorylation of CREB is increased. Furthermore, this transcription factor regulates long-lasting effects of NO in neurons (Contestabile 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor cAMP response element-binding protein (CREB) plays an important role in each of these processes (Finkbeiner et al, 1997;Ji and Rupp, 1997;Carlezon et al, 1998;Milner et al, 1998;Silva et al, 1998;Anderson and Seybold, 2000). Within the hippocampus and other brain regions, CREB activation after brief stimulation (Յ3 min) is primarily mediated by calcium entry via L-type calcium channels (with a smaller component attributable to NMDA receptors) (Sheng et al, 1991;Deisseroth et al, 1996;Mermelstein et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the expression of phosphorylated CREB was involved in the temporal effects of hyperalgesia in inflammatory pain. 23 For instance, an increase in the expression of p-CREB occurred in the hindpaw of rats after subcutaneous injection of carrageenan, formalin, or complete Freund's adjuvant. 19,23,24 Those rats who suffered from neuropathic pain demonstrated a similar phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…23 For instance, an increase in the expression of p-CREB occurred in the hindpaw of rats after subcutaneous injection of carrageenan, formalin, or complete Freund's adjuvant. 19,23,24 Those rats who suffered from neuropathic pain demonstrated a similar phenomenon. 12,25 In contrast, Miletic et al reported that there were no differences in CREB content between control and study animals.…”
Section: Discussionmentioning
confidence: 99%